2020
DOI: 10.2147/ijwh.s267675
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge of the Ovulatory Period and Associated Factors Among Reproductive Women in Ethiopia: A Population-Based Study Using the 2016 Ethiopian Demographic Health Survey</p>

Abstract: Purpose In the era of increasing health risks, refusals, discontinuations, and with high unmet needs for modern contraception, assessing knowledge of the ovulation period and identifying its associated factors among reproductive women are crucial to recommend natural family planning methods as an option. So, the aim of this Demographic Health Survey analysis was to assess knowledge of the ovulation period and its associated factors among reproductive women in Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 23 publications
14
25
1
Order By: Relevance
“…This is supported by a study in Ghana [ 16 ] and the USA [ 15 ]. A study conducted in Ethiopia using EDHS also supported our finding even though that study used simple logistic regression analysis without adjusting for community-level factors [ 20 ]. The reason for this association could be as age is increased, exposure to different reproductive related issues is increased that lets women gain more knowledge.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is supported by a study in Ghana [ 16 ] and the USA [ 15 ]. A study conducted in Ethiopia using EDHS also supported our finding even though that study used simple logistic regression analysis without adjusting for community-level factors [ 20 ]. The reason for this association could be as age is increased, exposure to different reproductive related issues is increased that lets women gain more knowledge.…”
Section: Discussionsupporting
confidence: 79%
“…Only one study reported the prevalence of knowledge of the ovulation period (i.e. 23.6%) which used the Ethiopian Demographic and Health Survey (EDHS) 2016 [ 20 ]. The previous study did not consider the community-level factors (only the individual-level factors were analyzed; even they did not use multilevel analysis which is appropriate for hierarchical data), there was no weighting to account for survey design, and essential variables were missed such as media exposure that plays a key role for the provision of information.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaires were adapted by EDHS from the DHS Program’s standard Demographic and Health Survey questionnaires to reflect the population and health-related issues relevant to Ethiopia. The details about the DHS methodology are published elsewhere, 26 , 27 and also available at http://www.dhsprogram.com/ . In this study to make the article more objective, we had read the STROBE statement-checklist of items that should be included in reports of cross-sectional studies and we have addressed each thing listed on the check list.…”
Section: Methodsmentioning
confidence: 99%
“…Women who do not know when they ovulate or how long the egg or sperm could live in a woman's body might have a low insight of their risk for pregnancy, and this could negatively influence their sexual behaviors and contraceptive use [36]. On the other hand, this DHS result was in congruent with [38].…”
Section: Discussionmentioning
confidence: 97%
“…This result signifies that greater than half of women are at risk to be pregnant with in their postpartum period. The possible reason might be due to the women's low awareness on their ovulatory period [38], poor knowledge on their fertile window and fertile period [36,[39][40][41][42], and difference in breastfeeding practices [43][44][45]. Women who do not know when they ovulate or how long the egg or sperm could live in a woman's body might have a low insight of their risk for pregnancy, and this could negatively influence their sexual behaviors and contraceptive use [36].…”
Section: Discussionmentioning
confidence: 99%